Synthesis of Single‐Phase Gd‐Doped Ceria Nanopowders by Radio Frequency Thermal Plasma Treatment. Issue 5 (10th April 2014) - Lee, Mi‐Yeon; Song, Min‐Kyung; Kim, Jeong‐Soo; Seo, Jun‐Ho; Kim, Min‐Ho; Butt, D.
<x xml:space="preserve">Abstract</x> Gd‐doped ceria nanopowders were synthesized using Radio Frequency (RF) thermal plasma. The powders were prepared by ball‐milling Gd2O3 and CeO2 powders of several tens of μm in size at the cation ratio of 8:2 and 9:1. The prepared precursors were treated by RF thermal plasma at a plate power level of ~140 kVA, and then, small‐sized powders (~50 nm) were retrieved by filtration. Transmission Electron Microscopy, Electron Energy Loss Spectroscopy, and Selected‐Area Electron‐Diffraction images of the as‐synthesized powders showed that Gd atoms were incorporated into the CeO2 particles. In addition, no crystalline peak for Gd2O3 appeared in the X‐ray diffraction patterns of the as‐synthesized powders, which is attributed to the solid solution of Gd3+ into the CeO2 lattices. Finally, Inductively Coupled Plasma‐Optical Emission Spectrometry analysis data revealed relatively small changes within 3 at.% in the cation composition between the ball milled powder mixtures and the nanoscale powders prepared from these mixtures.